Blessed Archbishop Oscar Romero, martyr of the Diocese refoundation - Osorio Torres, Juan Alberto (2016)
The Archbishop Oscar Romero was assassinated because he decided to legitimize and to accelerate, in his archdiocese and in his society, the transit from vertical, asymmetrical to another more horizontal and community pastoral model, on the relationship between pastors and faithful, in the exercise of authority and the ministry in the diocese. From the perspective of religious anthropology, and from still incipient diocese anthropology, the author conceptualizes and explains that fact as a real and effective reestablishment of the diocese. The author proposes such a process, as a reference for understanding the past of the diocese and the future of the Church, as a paradigm to foresee and to route the current functioning of this organizational unit within the framework of the structural reform of the Church convened three years ago by Pope Francis.